Implementasi Prinsip-Prinsip Ekonomi Syariah Dalam Bisnis Ritel Pada Dhuafa Mart Air Tiris - Zakir, Muhammad; Mairiza, Diany; Assyifa, Zubaidah; Winario, Mohd; Amalia, Nala; Putri, Berliana (EL-EMIR Institute, 2025)
This research aims to analyze the implementation of sharia economic principles in the retail business run by Dhuafa Mart Air Tiris. The sharia economic principles that are the focus include justice, transparency and benefit to the surrounding community, especially in supporting the economy of the poor. The research method used is a descriptive qualitative approach with data collection techniques through interviews, direct observation and documentation. The research results show that Dhuafa Mart Air Tiris has implemented several sharia economic principles, such as a transparent transaction system without usury, as well as a sharia contract-based cooperation pattern between the management and business partners. Apart from that, most of the profits obtained are allocated to social programs and economic empowerment for underprivileged communities. The discussion revealed that this practice not only supports sustainable business growth but also creates a significant social impact in the surrounding environment. This research concludes that the implementation of sharia economics in the retail business can become a business model that is not only profit-oriented but also provides real benefits for society. This is relevant for adoption by other business actors who want to run business with an ethical and sustainable approach in accordance with sharia values.